Analysis of Emotional Suppression and Marital Distress in the First Five Years of Marriage - Syifa Fadhillah, Tiara; Ratnasari, Yudiana (KnE Social Sciences, 2022)
Emotional suppression is an emotion regulation strategy that is often used in Eastern or Asian cultures like in Indonesia. Emotional suppression can be related to various outcomes in marital relationships such as marital distress. This research explored the association between emotional suppression and marital distress in individuals during their first five years of marriage. 1770 married participants from various regions in Indonesia participated (mean marriage length = 23.49 months). The research variables were measured using the Emotional Regulation Questionnaire (ERQ) and the Revised Dyadic Adjustment Scale (RDAS). Emotional suppression and marital distress were found to be negatively correlated. Differences in the norms in various situations across the culture seemed to influence the result. Inferential statistics were calculated to determine whether there was a significant difference in individual marital distress levels based on gender, the number of children, residential status, and changes in sexual activity during the Covid-19 pandemic. Keywords: marital distress, emotional suppression, early marriage, Covid-19 pandemic